Case: Southern Bank Berhad (SBB) / Amran Tamat, Mohd Fadzli Masleh and Zaidah Kassim - Tamat, Amran; Masleh, Mohd Fadzli; Kassim, Zaidah (Faculty of Business and Management, 2001)
Southern Bank Berhad (SBB), an anchor bank, commenced business in Penang in 1965. Since 1978, its corporate headquarters have been relocated to Kuala Lumpur. The SBB group is principally involved in banking, stockbroking, fund management and finance and financial related business locally and abroad that will soon extend to include merchant banking. The recent economic turmoil that hit Malaysia (1997-1998), has affected the financial industry and SBB experienced the same. Efforts were made by the government to minimized the impact with drastic currency control measures via fixing RM3.80 against USD1. Now the economy is recovering but there are still certain issues that need to be attended. Recent issues on globalization placed an impact in the business world. Competition among business is expected to grow due to unlimited transactions especially with the existence of advanced information technology. Bank Negara Malaysia (BNM) reduced the number of domestic banks to only 10 under its Bank Consolidation Programme. This move was initiated to make the bank strong enough to face the competitive globalized economy. SBB is the one of the 10 anchor banks.